Recent Advances in Water and Wastewater Treatment with Emphasis in Membrane Treatment Operations - Zouboulis, Anastasios (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
The present Special Issue brings together recent research findings from renowned scientists in the field of water treatment and assembled contributions on advanced technologies applied to the treatment of wastewater and drinking water, with emphasis on novel membrane treatment technologies. 12 research contributions have highlighted various processes and technologies, which can achieve effective treatment and purification of wastewater and of drinking water, aiming (occasionally) for water reuse. The main topics which are analyzed are the use of novel type membranes in bioreactors, the use of modified membranes, for example using vacuum membrane distillation, the fouling of membranes, the problem of arsenic, antimony and chromium contamination in groundwaters and its removal and the use of novel technologies for more efficient ozonation.